Analisis Semantik Sinonim Tomodachi, Yuujin, dan Nakama Dalam Kalimat Bahasa Jepang - Nardi Sentosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
This research was about a synonym of tomodachi, yuujin, and nakama in Japanese.Tomodachi, yuujin, and nakama have similar meaning in Japanese, that is „friend‟, but the usageis different in sentence, depend on the context and situation of sentence. The purpose of thisresearch wants to know of the meaning and similar meaning of tomodachi, yuujin, and nakama.The collecting data from some Japanese dictionary, Japan movie, and Japanese books relatedwith this research.Keywords : Synonym, tomodachi, yuujin, nakama, meaning, sentences.